2017
DOI: 10.1111/apha.12857
|View full text |Cite
|
Sign up to set email alerts
|

Alpha adrenergic receptor blockade increases capillarization and fractional O2 extraction and lowers blood flow in contracting human skeletal muscle

Abstract: Aim To assess the effect of elevated basal shear stress on angiogenesis in humans and the role of enhanced skeletal muscle capillarization on blood flow and O2 extraction. Methods Limb haemodynamics and O2 extraction were measured at rest and during one‐leg knee‐extensor exercise (12 and 24 W) in 10 healthy untrained young men before and after 4‐week treatment with an α1 receptor‐antagonist (Terazosin, 1–2 mg day−1). Corresponding biopsies were taken from the m. vastus lateralis. Results Resting leg blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(101 reference statements)
1
21
0
Order By: Relevance
“…Future studies could assess the effects of acute BP lowering per se (via alpha‐adrenergic blockade; see (Mortensen et al. ) on individual muscle NIRS responses to more thoroughly test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies could assess the effects of acute BP lowering per se (via alpha‐adrenergic blockade; see (Mortensen et al. ) on individual muscle NIRS responses to more thoroughly test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…3), and our use of an effective dose/selective b 1 -blocker (without peripheral vascular effects) strongly support a cause-effect relationship between acute lowering of cardiac pump function and augmented O 2 extraction in the active leg muscles. Future studies could assess the effects of acute BP lowering per se (via alpha-adrenergic blockade; see (Mortensen et al 2017) on individual muscle NIRS responses to more thoroughly test this hypothesis.…”
Section: Effects Of Esmolol On Exercising Muscle O 2 Saturationmentioning
confidence: 99%
“…In illicit private use, possible overdosing cannot be prevented. It is still unknown how hypoxia/PHDi use influences the long‐term mitochondrial function or muscle capillarization . Therefore, clinicians will have to take PHDi misuse into account when unexplained high haematocrits are detected as the latter has many unfavourable effects on arterial wall properties and haemostasis …”
Section: Is There a Risk Of Roxadustat Abuse?mentioning
confidence: 99%
“…It is still unknown how hypoxia/PHDi use influences the longterm mitochondrial function or muscle capillarization. 27 Therefore, clinicians will have to take PHDi misuse into account when unexplained high haematocrits are detected as the latter has many unfavourable effects on arterial wall properties and haemostasis. 28 In conclusion, the new 'wonder drug' PHDis have the potential to replace recombinant Epo in anaemia treatment in a multitude of (pathologic) conditions and thereby improve the individual's quality of life.…”
Section: Roxadustat Abuse?mentioning
confidence: 99%
“…Recent insights into the physiology of muscle metabolism may have implications for angiotherapeutic approaches, for example in peripheral arterial disease (PAD). Mortensen et al found that daily pharmacological treatment with an α‐adrenergic receptor blocker induced vascular proliferation in human skeletal muscle, likely due to an increase in shear stress. The increase in capillarization was associated with an increased fractional O 2 extraction, a lower blood flow and lower venous lactate levels in an exercising leg.…”
mentioning
confidence: 99%